RETRACTED: Teaching style restricting activity in classes: students’ attitudes with diverse temperament structures as an element of psychology of sustainability - Pronenko Evgeny; Pushkareva Polina; Zaporozhets Diana; Starygina Vlada (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001